How I feel when I hear no! - Farzam, Ronit (Magination Press, 2024)
"Uses imaginative metaphors to explore a child's anger when his mom tells him "no." Do you know how I feel when I hear NO? Kids hate the word "no"! It can make them feel mad and sad, turning them into a dragon that breathes fire, a mischievous wizard, and a raging volcano. It can make them want to destroy everything in their path. With a parent's help, together they can find the best way to turn a NO into a YES. Includes a Reader's Note with more information about helping children cope with big feelings associated with hearing "no.""--Publisher.